Iso-Partricin, an Aromatic Analogue of Amphotericin B: How Shining Light on Old Drugs Might Help Create New Ones - Paweł Szczeblewski; Justyna Górska; Witold Andrałojć; Patryk Janke; Karolina Wąsik; Tomasz Laskowski (MDPI AG, 2021)
Partricin is a heptaene macrolide antibiotic complex that exhibits exceptional antifungal activity, yet poor selective toxicity, in the pathogen/host system. It consists of two compounds, namely partricin A and B, and both of these molecules incorporate two cis-type bonds within their heptaenic chromophores: 28Z and 30Z. In this contribution, we have proven that partricins are susceptible to a chromophore-straightening photoisomerization process. The occurring 28Z→28E and 30Z→30E switches are irreversible in given conditions, and they are the only structural changes observed during the experiment. The obtained all-trans partricin's derivatives, namely iso-partricins A and B, exhibit very promising features, potentially resulting in the improvement of their selective toxicity.